VIRTUOUS LEADERSHIP AND ITS RELATIONSHIP TO ETHICAL BEHAVIOR A CASE STUDY IN MESOPOTAMIA GENERAL COMPANY FOR SEEDS (World Economics and Finance Bulletin, 2023)
The purpose of this research is to investigate the relationship between virtuous leadership and its relationship to the ethical behavior of a sample of employees working in the Mesopotamia General Company for Seeds, and this comes as an attempt to reduce or bridge the knowledge gap between the two research variables. In addition to trying to lay the correct and appropriate foundations for making leaders, relying on symbols emanating from Iraqi society that can be invested in order to be the most important capital for its profit-making organizations or for the provision of services. To achieve this, the researchers distributed 166 questionnaires to a number of employees in the Mesopotamian Seed General Company, and the number of questionnaires retrieved was 161, while the number of questionnaires valid for statistical analysis was (158), with an average of (98%) of the retrieved questionnaires. Theoretical results showed that there is a knowledge gap to explain the nature of the relationship between virtuous leadership and ethical behavior in organizations in general and in the organization under study in particular.